Identification of a cross-reactive HLA-DRB1*0301-restricted CD4 T cell response directed against cholesterol-binding cytolysins from two different pathogens - Paschen, Annette; Song, Mingxia; Nguyen, Xuan-Duc; Osen, Wolfram; Schadendorf, Dirk; Geginat, Gernot (Microbes and infection, 2006)
Cholesterol-binding cytolysins constitute an evolutionarily conserved family of pore-forming proteins expressed by different Gram-positive pathogens. Listeriolysin O, one well-characterized member of the cytolysin family, is also known to induce specific CD4 and CD8 T cell responses upon infection of mice with Listeria monocytogenes. Here we describe an HLA-DRB1*0301-restricted listeriolysin O-derived T cell epitope that is conserved among several members of the cytolysin family. An HLA-DRB1*0301-restricted CD4+T cell line, established from spleen lymphocytes of L. monocytogenes-infected HLA-DRB1*0301-transgenic mice, cross-reacted with a homologous peptide from perfringolysin O, a cytolysin expressed by Clostridium perfringens. Ex vivo analysis of infected mice revealed an even broader cross-reaction of T cells with homologous peptides derived from perfringolysin O, streptolysin O, and cereolysin O. Interestingly, a cross-reactive memory CD4+T cell response against the homologous peptides derived from listeriolysin O and perfringolysin O could also be detected in the blood from healthy HLA-DRB1*0301+ human donors. Remarkably, this response was even present in donors who did not exhibit a memory T cell reactivity against a second, non-conserved HLA-DRB1*0301-restricted LLO-derived CD4 T cell epitope, suggesting that cytolysin-producing bacteria other than L. monocytogenes can stimulate a cross-reactive cytolysin-specific immunity.